Cross‐linked polyacrylates in post‐mining substrates: persistence and effects on plant growth. (21st February 2014) - Rodionov, A.; Nii‐Annang, S.; Fischer, T.; Gattinger, A.; Bens, O.; Raab, T.; Hüttl, R. F.; Goss, Michael
Abstract Application of hydrophilic polymers composed of cross‐linked polyacrylate can improve soil water‐holding capacity and accelerate the restoration of post‐mining substrates. In this work, we studied the persistence of a polyacrylate polymer incorporated into a soil and its impact on plant nutrients at a reclamation site of former lignite mining in Lusatia (Germany). In contrast to autumn application, the incorporation of the polymer enhanced the sequestration of plant‐derived carbon in the soil, which was reflected by a significant increase in the concentration of a lignin marker. Attenuated total reflexion–Fourier transform infrared spectra (ATR‐FTIR) and total elemental contents in the applied polymer suggested an intensive cation exchange between the polymer framework and the soil‐forming substrate. In addition, there was an enrichment of carbonaceous material, which seems to reduce the swelling and thus the water‐holding capacity of the cross‐linked polyacrylate. Conversely, this process protected the polymer structure from rapid decomposition.